HUBUNGAN TRIGLISERIDA TIDAK PUASA DENGAN KEJADIAN STROKE ISKEMIK - Leny Wardaini, Dina Listyaningrum, Khairul Putra Surbakti, Darulkutni Nasution (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION ISCHEMIC STROKE REMAINS A MAJOR HEALTH PROBLEM AND A LEADING CAUSE OF MORTALITY AND DISABILITY THERE ARE MANY RISK FACTORS OF ISCHEMIC STROKE AND ONE OF THEM IS TRIGLYCERIDE EXPERIMENTAL STUDY PROVIDE EVIDENCE OF AN ASSOCIATION BETWEEN ISCHEMIC STROKE AND INCREASE LEVEL OF TRIGLYCERIDE GENERALLY TRIGLYCERIDE MEASURED IN THE FASTING STATE TO AVOID VARIABILITY BUT MANY STUDIES SHOW THAT NON FASTING TRIGLYCERIDE CAN ASSOCIATE WITH ISCHEMIC STROKE INCIDENT